Analisis Penerapan Terapi Murottal Pada Ibu Post Seksio Sesaria Atas Indikasi Riwayat Penyakit Jantung (Supraventricular Tachycardia) : Laporan Kasus - Rini Rahmayanti (Jurnal Keperawatan Muhammadiyah, 2019)
In the world according to WHO 2014 there are (16%) SEKSIO SESARIA deliveries that exceed the recommended limits. Whereas in Indonesia according to the 2013 Riskesdas the method of cesarean section surgery was 9.8% of the total 49,603 births throughout 2010-2013. Based on the 2013 Riskesdas data in West Sumatra the rate of West Sumatra cesarean section delivery (14%) where the figure is almost close to the maximum WHO standard. One common complaint felt by post seksio sesaria mothers is surgical pain. The purpose of this study was to determine the analysis of the application of murottal therapy in post-secsio caesarea women on the indication of a history of heart disease to reduce postoperative pain in the obstetric room of RSUP Dr. M. Djamil Padang. Nursing implementation in accordance with the objectives and interventions that have been formulated. The implementation is carried out for 5 days, from 3-7 June 2018. Ny. A listens to the explanation, and demonstrates the explanation given, especially murottal Al-Qur'an therapy to reduce postoperative pain. From the results of observations and interviews that the author did, Ny.A understood what had been explained and demonstrated. It is hoped that this research will be useful for health workers to be able to apply murottal therapy as one of the complementary therapies in treating post-cesarean patients.